STUDENTS WITH LANGUAGE LEARNING DISABILITIES AND DIFFICULTIES IN A FOREIGN LANGUAGE CLASSROOM - Ivančević Otanjac, Maja (Specijalna edukacija i rehabilitacija, 2016)
The aim of this paper is to present a brief review of the factors significant for foreign language learning, with special emphasis on students with language learning disabilities and difficulties. The paper overviews the available literature on how native language skills and foreign language aptitude influence the success in foreign language acquisition. Also, it points out the importance of teachers’ role and appropriate teaching modifications and methods suitable for students who have difficulties in foreign language learning.